Pendekatan Digital Dalam Pendidikan Agama Kristen: Menjembatani Jarak, Memperkuat Iman - Maabuat, Paul Stefan (DELAHA: Journal of Theological Sciences, 2025)
Amid rapid technological advancements, the world of education is undergoing significant transformation. The integration of digital technology into various aspects of life, including education, has opened up numerous new opportunities. Christian Religious Education, Which plays a vital role in shaping students’ character and morals, is no exception. As technologhy continues to evolve, the application of digital approaches in Christian Education emerges as a compelling topic, particularly regarding innovative methods for conveying religious teachings in ways that remain relevant to contemporary developments. Digital approaches not only influence how material is delivered but also shape how students can access, process, and reflect on religious teachings more broadly and interactively. This study employs library research to examine the implementation of digital approaches in Christian Religious Education. Library research involves collecting data from a variety of relevant literature sources, including books, journal articles, research reports, and other academic materials related to Christian education and digital technology. The adoption of digital methods in Christian Religious Education has created significant opportunities to enrich the learning experience and expand the reach of religious instruction. Tools such as Bible apps, e-learning platforms, and social media enable Christian teachings to be delivered in ways that are more flexible, engaging, and accessible, particularly for younger generations who are increasingly connected to technology.